Glucose Metabolism and Glucose Transporters in Breast Cancer - Shin, Eunah; Koo, Ja Seung (Frontiers in Cell and Developmental Biology, 2021)
Breast cancer is the most common malignancy in women worldwide and is associated with high mortality rates despite continuously advancing treatment strategies. Glucose is essential for cancer cell metabolism owing to the Warburg effect. During the process of glucose metabolism, various glycolytic metabolites, such as serine and glycine metabolites, are produced and other metabolic pathways, such as the pentose phosphate pathway, are associated with the process. Glucose is transported into the cell by glucose transporters, such as GLUT. Breast cancer shows high expressions of glucose metabolism related enzymes and GLUT, which are also related to breast cancer prognosis. Triple negative breast cancer, which is a high-grade breast cancer, is especially dependent on glucose metabolism. Breast cancer also harbors various stromal cells such as cancer associated fibroblasts and immune cells as tumor microenvironment, and there exists metabolic interaction between these stromal cells and breast cancer cells as explained by reverse Warburg effect. Breast cancer is heterogeneous, and consequently its metabolic status is also diverse, which is especially affected by molecular subtype, progression stage, and metastatic site. In this review, we will focus on glucose metabolism and glucose transporters in breast cancer, and we will additionally discuss their potential applications as cancer imaging tracers and treatment targets.